2017
DOI: 10.1016/j.ultsonch.2016.06.037
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-synergized electrostatic field extraction of total flavonoids from Hemerocallis citrina baroni

Abstract: The total flavonoids from Hemerocallis citrina baroni are regarded as a green and natural health care product with many beneficial impacts on human health. In this study, ultrasound-synergized electrostatic field extraction (UEE) of the total flavonoids (TF) from H. citrina was investigated. Significant independent variables of the extraction, including the electrostatic field, ultrasonic power, ethanol concentration and extraction time, were optimized using the Box-Behnken (BB) method, and the optimal extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…However, the extracted emodin may be degraded and its structure may be destroyed when the time is too long in the ultrasonic surrounding [49]. On effect of ethanol concentration, the effect tendency was consistent with the reports on the extraction of orientin and avonoids [50,51]. On one hand, dielectric constant of extraction reduces with the amount of ethanol increasing, and then solvent solubility and diffusion of target components are improved, which in turn result in the high yield of emodin [52].…”
Section: Discussionsupporting
confidence: 83%
“…However, the extracted emodin may be degraded and its structure may be destroyed when the time is too long in the ultrasonic surrounding [49]. On effect of ethanol concentration, the effect tendency was consistent with the reports on the extraction of orientin and avonoids [50,51]. On one hand, dielectric constant of extraction reduces with the amount of ethanol increasing, and then solvent solubility and diffusion of target components are improved, which in turn result in the high yield of emodin [52].…”
Section: Discussionsupporting
confidence: 83%
“…Flavonoids are a kind of compounds widely distributed in plants as secondary metabolites (Zakaryan et al, 2017). An increasing number of studies have reported the extraction methods of flavonoids from different plant sources (Liu et al, 2016;Jing et al, 2016;Wang et al, 2017;Yang et al, 2017;Yu et al, 2017). Enzymeassisted extraction is established as an emerging technique to accelerate the release of bioactive components from plant materials, due to its advantages of high extraction yield, environmental compatibility, low energy requirement and simplified manipulation (Chen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…To further investigate the practicability of the proposed method, a comparison with other methods existed for flavonoid extraction was performed in terms of extraction method, solvent, extraction time, analysis method and time (Table ). It was found that these reported methods required frequently a large amount of sample (more than 0.5 g) and extraction solvent (more 10 mL) while the current industrial MCM‐41‐MMSPD extraction method only required the milligram amounts of sample (25 mg) and reagent (1.25 mL) . In addition, most of these methods mainly focused on a few flavonoids or total flavonoids, which were insufficient for evaluation quality of TCMs with multi‐compounds.…”
Section: Resultsmentioning
confidence: 99%
“…UHPLC is selected in our study to realize the rapid analysis and determination of multi‐components in Pollen typhae based on its superiority of small injection volume, low mobile phase consumption, and short analysis time. Based on the present analysis methods, there are series of extract methods for herbal products such as heating reflux extraction , ultrasound method, microwave extraction , and solid phase extraction . These methods usually require many samples and organic reagents, long extract period, high temperature or energy, and complex equipment.…”
Section: Introductionmentioning
confidence: 99%